Mental health policy development in Africa - O. Gureje; A. Alem
Mental health issues are usually given very low priority in health service policies. Although this is changing, African countries are still confronted with so many problems caused by communicable diseases and malnutrition that they have not woken up to the impact of mental disorders. Every country must formulate a mental health policy based on its own social and cultural realities. Such policies must take into account the scope of mental health problems, provide proven and affordable interventions, safeguard patients' rights, and ensure equity.